De novo p.Arg756Cys mutation of ATP1A3 causes an atypical form of alternating hemiplegia of childhood with prolonged paralysis and choreoathetosis. Issue 1 (December 2016) - Kanemasa, Hikaru; Fukai, Ryoko; Sakai, Yasunari; Torio, Michiko; Miyake, Noriko; Lee, Sooyoung; Ono, Hiroaki; Akamine, Satoshi; Nishiyama, Kei; Sanefuji, Masafumi; Ishizaki, Yoshito; Torisu, Hiroyuki; et al.
Abstract Background Alternating hemiplegia of childhood (AHC) is a rare neurological disorder that manifests recurrent attacks of hemiplegia, oculogyric, and choreoathetotic involuntary movements.De novo mutations inATP1A3 cause three types of neurological diseases: AHC; rapid-onset dystonia-Parkinsonism (RDP); and cerebellar ataxia, areflexia, pes cavus, optic atrophy, and sensorineural hearing loss (CAPOS) syndromes. It remains to be determined whether or not a rare mutation inATP1A3 may cause atypical phenotypes. Case presentation A 7-year-old boy presented with recurrent symptoms of generalized paralysis since 1 year and 5 months of age. Hypotonia, dystonia, and choreoathetosis persisted with exacerbation under febrile conditions, but no cerebellar ataxia had ever evolved in 6 years. Whole-exome sequencing (WES) was performed to determine his genetic background, and mutations were validated by the Sanger method. Crude protein extracts were prepared from the cultured cells, and expression of the wild-type or mutant ATP1A3 proteins were analyzed by Western blotting. WES identified ade nov o pathogenic mutation inATP1A3 (c.2266C > T:p.R756C) for this patient. A literature overview of two reported cases with p.R756C and p.R756H mutations showed both overlapping and distinct phenotypes when compared with those of the present case. The expression of the mutant form (R756C) of ATP1A3 did not differ markedly from that of the wild-type and D801N proteins. Conclusions This study confirmed that p.R756C mutation ofATP1A3 cause atypical forms of AHC-associated disorders. The wide spectra of neurological phenotypes in AHC are linked to as-yet-unknown deficits in the functions of mutant ATP1A3.